Aktivitas Antioksidan dan Uji Organoleptik Yogurt dengan Penambahan Ekstrak Lamota (Salicornia europaea) - Munandar, Imam; Havied, Arief Rahman; Dwitya, Ning Ayu; Akramullah, Muh.; Jatnika, Ahmad Reza; Amalyadi, Rezki (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to determine the effect of adding lamota (Salicornia europaea) extract on the antioxidant activity and organoleptic properties of yogurt. Yogurt is made by adding 5%, 10% and 15% lamota extract. Tests carried out included antioxidant activity tests using the DPPH method and organoleptic tests (color, aroma, taste, texture and overall acceptability) with 15 panelists. The results showed that the addition of lamota extract had a significant effect on the antioxidant activity of yogurt, with the highest value in the treatment being 15% (11.21%). Organoleptic tests showed significant differences in aroma attributes, where the addition of 15% lamota extract was less liked by panelists. The color, taste and texture attributes did not show significant differences between treatments. Overall, yogurt with the addition of 15% lamota extract was most liked by the panelists. This research shows the potential for using lamota as a functional additive in making yogurt to increase antioxidant activity.